Uji Insektisida Ekstrak Daun Zodia (Evodia Sauveolens) terhadap Nyamuk Anopheles Sp. - Sugiarto I Hamzah; Aprilia, Dina Vita; Ningrum, Shintia Puspita; Kurniawan, Fajar Bakti; Hartati, Risda; Sahli, Indra Taufik; Asrianto Asrianto; Whardani, Afika Herma; Purwati, Rina (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Zodia leaves (Evodia suaveolens) are endemic plants of Indonesia originating from Papua, widely known for their natural mosquito-repelling properties. Traditionally, local communities use these leaves by rubbing them directly onto the skin to avoid mosquito and insect bites. Zodia leaves contain active compounds that produce a distinctive aroma disliked by mosquitoes, making them an effective natural repellent. One of the diseases transmitted by mosquitoes is malaria, which attacks human red blood cells and is spread through the bite of Anopheles mosquitoes. A high population of mosquito larvae and adults in an area increases the risk of malaria transmission. Although vector control is commonly carried out using synthetic insecticides that provide rapid results, these chemicals may lead to negative effects such as insecticide resistance in mosquitoes and environmental pollution. Therefore, safer and more sustainable alternatives for vector control are urgently needed. The use of zodia leaves as a natural mosquito repellent is considered effective and environmentally friendly. This potential should be further explored as an alternative solution in the prevention of vector-borne diseases, particularly malaria, using an approach that prioritizes public health and environmental sustainability.